Penguatan Budaya Keselamatan Berkendara melalui Seminar Safety Riding dan Layanan Servis Kendaraan Gratis di Desa Kaliurip Purworejo - Aci Primartadi; Dwi Jatmoko; Mike Elly Anitasari; Yuli Widiyono; Dimas Nanda Wibowo; Muhammad Arsyady (Lembaga Pengembangan Kinerja Dosen, 2026)
Riding safety is a key issue in efforts to reduce traffic accident rates. This issue is evident among the residents of Kaliurip Village, where the majority rely on motorcycles as their primary mode of transportation. Observations and coordination with the village government revealed that residents still lack sufficient understanding regarding the importance of periodic vehicle inspections, the use of safety gear, and the practice of orderly traffic behavior. Therefore, this Community Service (PkM) initiative aims to enhance residents' knowledge, awareness, and behavior through a